Abnormal endometrial changes in the rat estrogen hormone and chorionic - Arias Stella, Javier (2015)
The administration of human chorionic hormone, and estrogen, to normal rats, produces an atypical endometrial histological picture, characterized by simultaneous presence of secretory and proliferative changes. The core of epithelial cells shows that overall a more normal appearance and occasionally reaching vesicular large. Abnormal box can not be induced by treating rats with normal estrogen or chorionic administered alone or neutered animals both hormones. A similar alteration, however, is when ovariectomized rats are treated with large doses of estrogen and progesterone. The pathogenesis and the relationship of this condition with certain endometrial changes observed in humans briefly discussed.